Macrourimegatrema brayi n. gen., n. sp. (Digenea: Opecoelidae) from four species of deep-sea macrourid fishes from the Gulf of Mexico and Caribbean Sea, with a list of endohelminths reported from species of Bathygadus and Gadomus (Macrouridae) - Blend, Charles K.; Dronen, Norman O.; Armstrong, Howard W. (Zootaxa, 2004)
Macrourimegatrema brayi n. gen., n. sp. (Digenea: Opecoelidae: Plagioporinae) is described from the pyloric ceca and intestines of 4 species of bathygadine macrourid fishes collected from deep waters of the Gulf of Mexico and off Colombia and Panama. Macrourimegatrema n. gen. can be distinguished from all other genera in the subfamily by possessing a combination of the following diagnostic characteristics: an atypically large elongate body; a short, distinct forebody separated from a long hindbody by a distinct constriction at the level of the acetabulum; a terminal, funnelshaped oral sucker; nearly equatorial ovary and testes and an unusual tubular excretory vesicle that winds between the 2 tandem testes. Macrourimegatrema n. gen. is most similar to the genus Anabathycreadium, but the former differs in having a smaller body size (6,000 vs 15,500 m); a funnelshaped oral sucker; a slightly protuberant acetabulum; suckers of equal size; an oval pharynx (rather than being ring-shaped); ceca that terminate some distance from the posterior extremity; a smaller cirrus sac that reaches only a short distance postacetabularly (rather than reaching to the level of the ovary); a genital pore that is bifurcal to slightly prebifurcal (rather than being at the posterior margin of the pharynx); numerous, small, follicular vitelline follicles that approach the level of the acetabulum anteriorly (rather than terminating well short of the level of the acetabulum); an ovary that is immediately pretesticular (rather than being far removed anteriorly from the anterior testis) and M. brayi n. gen., n. sp. has an unusual tubular excretory vesicle that winds between the 2 testes. Species of opecoelids are expected to utilize either a crustacean or fish second intermediate host, and the lack of fish reported for the food preferences of members of Bathygadinae studied here suggest that M. brayi n. gen., n. sp. probably infects its host through ingestion of a near-bottom pelagic crustacean. The precedence of using general body morphology of the species or its conformation to the characteristics of the 4 subfamilies of Opecoelidae is discussed.